2011
DOI: 10.1186/1471-2091-12-10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of acetaldehyde-induced deactivation of microbial lipases

Abstract: BackgroundMicrobial lipases represent the most important class of biocatalysts used for a wealth of applications in organic synthesis. An often applied reaction is the lipase-catalyzed transesterification of vinyl esters and alcohols resulting in the formation of acetaldehyde which is known to deactivate microbial lipases, presumably by structural changes caused by initial Schiff-base formation at solvent accessible lysine residues. Previous studies showed that several lipases were sensitive toward acetaldehyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Another reason for the reduction in activity might be the generation of acetaldehyde from the tautomerization of vinylalcohol when using vinyl ester as acyl donor and/or the presence of 1-butanol. It has been reported that this leads to a deactivation of various lipases [58][59][60]. This deactivation is more severe under continuous flow conditions than under batch condition, which might due to the higher reactants concentration as well as generation of a larger amount of acetaldehyde in total during the fixed-bed reaction.…”
Section: Application Of Selected Biocatalysts In Fixed-bed Transestermentioning
confidence: 95%
“…Another reason for the reduction in activity might be the generation of acetaldehyde from the tautomerization of vinylalcohol when using vinyl ester as acyl donor and/or the presence of 1-butanol. It has been reported that this leads to a deactivation of various lipases [58][59][60]. This deactivation is more severe under continuous flow conditions than under batch condition, which might due to the higher reactants concentration as well as generation of a larger amount of acetaldehyde in total during the fixed-bed reaction.…”
Section: Application Of Selected Biocatalysts In Fixed-bed Transestermentioning
confidence: 95%
“…There were two possible reasons for the improvement. First, it was reported that the acetaldehyde produced from enol donors was responsible for lipases deactivation . This might be one of the advantages of using our newly designed substrates.…”
Section: Resultsmentioning
confidence: 91%
“…(Berger andFaber, 1991, Franken et al, 2011). For example, C. cylindracea lipase forms a Schiff base with lysine residue, thus limiting its use (Franken et al, 2011). The poor activity of these enzymes could be accounted for.…”
Section: Methodsmentioning
confidence: 99%